Anticipation of quarterly earnings announcements - Whaley, Robert E.; Cheung, Joseph K. (Journal of Accounting and Economics, 1982)
This study tests Chicago Board Options Exchange efficiency by examining option price behavior in the weeks surrounding a firm's quarterly earnings announcement. The evidence presented here suggests that a first-order autoregressive seasonal process describes quarterly earnings behavior and demonstrates that the information content of an earnings announcement is fully incorporated in option prices by the end of the announcement week.